Análise da expressão protéica de moléculas de adesão celular em melanomas cutâneos - Fernandes, Mariana [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Cutaneous melanoma is a malignancy caused by the uncontrolled proliferation of melanocytes. Has been increasing in incidence and mortality over the years. This type of tumor may arise in the skin or any other place where there was migration of neural crest cells. Melanocytes are located in the basal layer of the epidermis forming the epidermal melanin unit, involving a melanocyte to 36 keratinocytes. The proliferation of melanocytes depends on this relationship with the keratinocytes, gap junctions, E-cadherin and desmoglein. The basal membrane is responsible for promoting the integrity of the skin, their adhesion structures shown to be altered in several skin diseases. Some molecules that play the role of adherence in this membrane are the laminins, type IV collagen and type XVII and perlecan. Analysis of protein expression of cell adhesion molecules in melanoma by immunohistochemistry on tissue microarray (TMA). We selected paraffin blocks of patients who were diagnosed with cutaneous melanoma in the period 1995 to 2010, reaching a sample of 124 cases. All these have gone through review of preparation for subsequent histological analysis of tissue microarray (TMA). The protein expression will be analyzed by immunohistochemistry, using markers anti-laminin, anti-collagen type IV and type XVII and anti-perlecan. There was a predominance of female patients, Caucasians and southeastern Brazil. There were frequent in type of extensive superficial ulcers with Breslow depth greater than 4 mm, Clark level IV and mitotic index greater than 6 mitoses per cga. The patients, most of them were female with mean age of 57.13 years and Caucasian. The most frequent histological type was extensive superficial followed by acral lentiginous. Predominated cases very deep, with Breslow thickness greater than 4 mm, Clark IV, ulcerated and on average by 9 cga mitosis, leading to worse prognosis in this sample. It...(Complete abstract click electronic access below)

O melanoma cutâneo é uma neoplasia maligna originada pela proliferação desordenada de melanócitos. Tem apresentado um aumento na sua incidência e mortalidade com o passar dos anos. Este tipo de neoplasia pode surgir na pele ou em qualquer outro local em que houve migração das células da crista neural. Os melanócitos localizam-se na camada basal da epiderme formando a unidade pigmentar epidermal, associando um melanócito e 36 queratinócitos. A proliferação dos melanócitos depende desta relação com os queratinócitos, por junções comunicantes, E-caderina e desmogleina. A zona de membrana basal é responsável por promover a integridade da pele, suas estruturas de adesão mostram-se alteradas em diversas doenças cutâneas. Algumas moléculas que desempenham a função de adesão nesta membrana são as lamininas, colágenos tipo IV e tipo XVII e perlecan. Análise da expressão protéica, de moléculas de adesão celular, em melanomas por estudo imunoistoquímico em arranjo tecidual de matriz (TMA). Foram selecionados blocos de parafina de pacientes que foram diagnosticados com melanoma cutâneo, no período de 1995 a 2010, chegando a uma casuística de 124 casos. Todos estes passaram por revisão da análise histológica para posterior confecção do arranjo tecidual de matriz (TMA). A expressão protéica será analisada por técnica de imunoistoquímica, usando os marcadores anti-laminina, anti-colágeno tipo IV e tipo XVII e anti-perlecan. Predominaram os pacientes do sexo feminino, caucasianos e da região Sudeste do Brasil. Houve maior frequência do tipo extensivo superficial ulcerado, com profundidade de Breslow maior que 4 mm, nível de Clark IV e índice mitótico maior que 6 mitoses por campos de grande aumento. Os pacientes, em sua maioria, eram do sexo feminino com idade média de 57,13 anos e caucasianos. O tipo histológico...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Melanoma; Colageno; Pele – Câncer; Laminina